A novel design of an energy analyzer for charged particles based on a non-uniform electrostatic field - Kambarova, Zh.T.; Saulebekov, A.O.; Kassymov, S.S. (Karagandy University of the name of academician E.A. Buketov, 2025)
A new design for an energy analyzer based on an axial symmetric non-uniform field has been proposed. Using the superposition method of a cylindrical field and second-type axially dodecapole, the electron-optical scheme for the energy analyzer has been developed. Numerical modeling of the electron-optical scheme of the device was performed, and its analytical characteristics were obtained. It is shown that the proposed design combines high resolution and effective luminosity. The results confirm the feasibility of using the developed device for studying charged particle beams in outer space.
Keywords: energy analyzer; non-uniform field; multipole; modeling; charged particle beams